Tinjauan Yuridis Undang-Undang Nomor 35 Tahun 2014 tentang Perlindungan Anak terhadap Adak dari Korban Tindak Pidana : Studi Lapangan di Komnas Perlindungan Anak Kabupaten Serang - Anita Wulandari; Ujang Hibar; Enjum Jumhana (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
The crime of rape and molestation is a form of violence against women. Children as part of the younger generation are the successors of the ideals of the nation's struggle as well as human resource capital for national development. That children have a very strategic position in the nation, state, society and family. Children are the mainstay of hope for the future of the nation, state, society or family. Therefore, their condition as children requires special treatment so that they can grow and develop naturally, both physically, mentally and spiritually. For this reason, children need to be protected from criminal acts that can affect their physical, mental and spiritual development. The problems and objectives of the research taken include: to determine the form of legal protection given to children from victims of rape/molestation, and to determine what are the obstacles in providing legal protection to children from victims of rape and molestation. The method used is the type/kind of normative research (normative juridical) with a statutory approach related to research material that has been decided by the Court which has permanent legal force, legal sanctions only on the perpetrators (boys), while there are none for female victims. Obstacles in providing protection for victims of rape and molestation are: Law Number 35 of 2014 concerning child protection does not regulate compensation for victims of rape/molestation (for recovery costs). Generally, people are reluctant to report incidents of rape/molestation, because of the shame and embarrassment of being known by the wider community.